Predictors of pregnancy intention among child marriage based on the theory of planned behavior - Javad Harouni; Naser Sharafkhani; Sahar Mehdipour birgani; Narges Roustaei; Moslem Sharifi; Seyed Fazel Zinat Motlagh (Health Science Monitor)
Background & Aims: The phenomenon of child marriages, or the marriage of children under the age of 18, jeopardizes the mental and physical health of millions of children and adolescents worldwide. This study aimed to investigate the predictors of pregnancy intention among child marriages using the theory of planned behavior in the city of Karun, Southwest Iran. Materials & Methods: A descriptive-analytical study was conducted on 344 child marriages in the city of Karun, located in Southwest Iran. The data collection tools consisted of a demographic information questionnaire and a structured theory of planned behavior questionnaire, which included questions related to attitude, subjective norms, perceived behavioral control, and behavioral intention. The collected data were analyzed using SPSS version 22. Results: All study participants had completed no more than a high school education, with 96.7% having only completed elementary or middle school. Additionally, 99% of participants were housewives. Of the child marriages surveyed, 50.3% reported intending to become pregnant before the age of 18. Attitude, subjective norms, and perceived behavioral control were found to predict 57% of the variance in intended pregnancy among child marriages. Among these factors, subjective norms had the strongest impact on intended pregnancy among child marriages. Conclusion: The results of this study showed a high prevalence of pregnancy intention below the age of 18 among child marriages who presented to healthcare centers, which could endanger their health. Given the correlation between the structured theory of planned behavior and intended pregnancy below the age of 18 in child marriage, educational strategies based on predictive factors can be used to educate women about respecting the appropriate age and conditions for pregnancy.